PERAN KOMPETENSI GURU PENGGERAK DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Sitti Rahma; Irwan Akib; Rukli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to investigate the role of competence of teacher motivators in enhancing student motivation in elementary schools. Through observation and interviews conducted at UPT SPF SD Inpres Karuwisi 2, it was found that teacher motivators have a significant impact on student motivation in learning. By implementing effective strategies such as providing praise and recognition, actively involving students, and maintaining communication with parents, teacher motivators are able to create a positive and motivating learning environment. This is supported by motivational theories from experts, such as Self-Determination Theory, Hierarchy of Needs Theory, Goal Setting Theory, and Social-Cognitive Theory. With competent teacher motivators, students experience improved motivation in learning, become motivated, confident, and achieve better academic performance. In conclusion, the competence of teacher motivators plays a crucial role in enhancing student motivation in elementary schools and positively influencing the overall development of students' potentials.